A new metal-organic framework constructed from tetracarboxylate: Structure, magnetism and simulation. Issue 2 (1st February 2017) - Wang, Fu-Min; Liu, Wei-Cong; Wu, Xi-Ren; Xu, Jing-Wen; Luo, Miao-Miao; Yang, Su-Zhen; Wu, Jia-Min; Li, Qing-Lin; Liu, Jian-Qiang
ABSTRACT: A new metal-organic framework of [Cu2 (L)(H2 O)2 ]·2DMF (1 ) (H4 L = quaterphenyl-3, 3′″, 5, 5′″-tetracarboxylic acid) has been prepared and characterized. It has the NbO-derived topology that was observed in MOF-505. Magnetic study reveals the overall antiferromagnetic interactions between neighboring Cu(II) ions in compound1 . In addition, we performed an optimization by semiempirical PM5 method simulations to investigate the loading of 5-FU to1 at the molecular level.